Scheduling battery usage in mobile systems. - Benini, L.
The use of multibattery power supplies is becoming common practice in electronic appliances of the latest generations. Economical and manufacturing constraints are at the basis of this choice. Unfortunately, a partitioned battery subsystem is not able to deliver the same amount of charge as a monolithic battery with the same total capacity. In this paper, we define the concept of battery scheduling, we investigate several policies for solving the problem of optimal charge delivery, and we study the relationship of such policies with different configurations of the battery subsystem. Experimental results, obtained for different kinds of current workloads, demonstrate that the choice of the proper scheduling can make system lifetime as close as 1% of the theoretical upper bound, that is, a monolithic power supply of equal capacity.
Keywords: Battery subsystem; Capacity; Electronic appliances; Manufacturing constraints; Monolithic battery; Monolithic power supply; Multibattery power supply; Transactions